Analisa Perkembangan Vilan Store sebagai Model Bisnis Gen Z di Era Digital - Andriansya, Muhamad Alif; Dordia Wahjudi, Putri Ichtiari; Prastika, Maulidya; Kurniasari, Nasywa Aliyah; Shafina, Viola (PUTRA JAWA PUBLISHER, 2025)
This research aims to analyze the development of Vilan Store as a business model operated by Gen Z in the digital era. Vilan Store is a business that sells items from the game Toram Online, utilizing digital platforms and social media to reach consumers. The objective of this study is to explore the development of Vilan Store during its participation in the Student Entrepreneurship Program (PKM), and the business model it applies in leveraging digital trends to sell virtual products. This study employs a qualitative approach with a case study method, involving in-depth interviews with managers and customers, along with observations of business operations. The findings show that Vilan Store has grown significantly due to the use of social media for marketing and customer communication, as well as the use of e-commerce platforms for more efficient transactions. This business model aligns well with the characteristics of Gen Z, who are accustomed to digital transactions and interactions. In conclusion, Vilan Store has capitalized on digital market opportunities with an innovative business model that meets the needs of the Gen Z market.